(untitled) (Journal of the College of Basic Education, 2022)
After its long journey in the corridors of the critics’ compilations, the rhetoricians research, and their attempt to maturation science of Badi’, as one of the sciences of rhetoric that requires standing at its arts and methods that contributed to the beauty of the poetic text and highlighting its goodness from its ugliness; and its quality from its shoddy; this research revealed to us the efforts of scholars, including critics and rhetorics, in directing the rhetorical effect that resulted from these Badi’i arts on which the poetic text was basedز ِs for our poet Yusef Al-Sayegh, he embodied the rhetorical aesthetics in his poetry, so these poems were an expressive means of the places of beauty and the feeling of it, then accurate methods appeared in his mind that diverted from the utopianism of the pious language, so he employed the beauty of the Badi ’in praising Christ (peace be upon him) for the decision of those who preceded him in The praise of the Prophet Muhammad (may God’s prayers and peace be upon him and his family). Al-Sayegh added to her the beauty of his soul, sparked his imagination and cleverness of mind, to form an accurate picture of Christ (peace be upon him) accepted by taste and reassured by the minds and sensations, and hearts revived, and it becomes more influential in the recipient